Irrigation in Africa in figures : (FAO, 2005)
The AQUASTAT programme was established to develop a comprehensive picture of water resources and irrigation in developing countries, and to give systematic, up-to-date and reliable information on water for agriculture and development. This report sets out an analysis of water availability and its use on the African continent and changes that have occurred over the last decade, with an emphasis on agricultural water use and management. The report includes a CD-ROM with detailed profiles on the situation in each of the 53 countries in Africa.